Pekerja Domestik dari Daerah Pinggiran di Kota Medan - Lubis, Anggreni Atmei (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
Mobility of the citizens due to domestic working which is commonly called as household assistant in Medan city, coming from marginal areas. Most of the workers leave for Medan in the morning and return home in the afternoon. However part of them live in Medan for weeks or months even years. They are coming from Tembung indicated by a large flow of bikers as long as Letda Soedjono Street contributing to traffic jammed on the crowded road. One of the some problems happening is over crowded which result in traffic jam. It is due to working they do for extra income to get financial suppot and for helping their husbans financing household. This work is not really demand a specific and difficult skill result of rely on the wowen instinct, patience, and work hard.